Self-assembly, thermotropic and lyotropic behaviour of synthetic branched-chain alkylmaltosides / Nur Asmak Nabila Saari - Nur Asmak Nabila , Saari (2018)
Maltose sugar (normally used widely in candy industry and intravenous injection) in this study is used as the hydrophilic headgroup attached to the Guerbet chain. The effect of chain branching on glycolipid thermotropic and lyotropic phases was investigated for a series of synthetic β-D-maltosides derived from Guerbet alcohols, whose total hydrocarbon chain length ranged from C8 to C24. Synthesis and characterisation of various branched-chain glycolipids have been attempted as these are suitable models for further study on the structure and mechanism of cell membrane. Since natural glycolipids compound have limited availability and require extensive syntheses, similar compounds that can mimic the property of natural materials were synthesised for applications in the field of biophysics and biotechnology. The branched-chain glycolipids have been reported to produce the inverse liquid crystal structures inducing various changes in the physicochemical properties of the disaccharide-based glycolipids self-assembly. The compounds were synthesised to a high purity and their liquid crystalline phases were characterised using differential scanning calorimetry (DSC), optical polarising microscopy (OPM), and small-angle X-ray scattering (SAXS). Thermal investigations of all anhydrous Guerbet maltosides showed that they do not form solid crystals but undergo a glass transition upon temperature change in the range of 35 to 53 °C. The glassy crystalline structure turns into the liquid crystalline structure upon heating or addition of water. In thermotropic studies, the lamellar phase formation is prominent in shorter chain length analogues while the longer chain compounds exhibit more frustrated form of self-assembly in the formation of metastable state, polymorphism and inverse bicontinuous cubic structure (Ia3d) as the synthesised maltosides possess two opposing features from the headgroup (energetic) and the chain branching (entropic) which are equally dominant, resulting in the self-assembly to become frustrated and compromised to give a particular thermotropic polymorphism. The clearing temperatures of these branched-chain maltosides are in the range of 138 to 233 °C. The high clearing temperatures are due to the extensive hydrogen bond network in the head group region. Lyotropic studies show that the phase formation is dominated by lamellar phase for the longer chain compounds. Normal micellar solution was also observed in the shortest chain length maltosides due to the enlargement in hydrated maltose headgroups as observed from the SAXS investigations.